Two-Year Follow-Up Study of the Relationship Between Brain Structure and Cognitive Control Function Across the Adult Lifespan - Hsieh, Shulan; Yang, Meng-Heng (Frontiers in Aging Neuroscience, 2021)
Age-related decline in cognitive control and general slowing are prominent phenomena in aging research. These declines in cognitive functions have been shown to also involve age-related decline in brain structure. Yet, most evidence in support of these associations is based on cross-sectional data. Therefore, the aim of this study is to contrast cross-sectional and longitudinal analyses to re-examine if the relationship between age-related brain structure and cognitive function are similar between the two approaches. One hundred and two participants completed two sessions with an average interval of 2 years. All participants were assessed by questionnaires, a series of cognitive tasks, and they all underwent neuroimaging acquisition. The main results of this study show that the majority of the conclusions regarding age effect in cognitive control function and processing speed in the literature can be replicated based on the cross-sectional data. Conversely, when we followed up individuals over an average interval of 2 years, then we found much fewer significant relationships between age-related change in gray matter structure of the cognitive control network and age-related change in cognitive control function. Furthermore, there was no ‘initial age’ effect in the relationships between age-related changes in brain structure and cognitive function. This finding suggests that the ‘aging’ relationship between brain structure and cognitive function over a short period of time are independent of ‘initial age’ difference at time point 1. This result of this study warrants the importance of longitudinal research for aging studies to elucidate actual aging processes on cognitive control function.